Artificial Intelligence (AI) for Sustainable Institutional Food Systems: Implementation of AI Tools for School Nutrition Program Management in the United States of America - Camaréna, Stéphanie (Frontiers in Sustainable Food Systems, 2022)
School food programmes can improve the nutritional status of communities and can be a powerful tool to transition to sustainable food systems through their purchasing methods and management of meals and waste. As an enabler or inhibitor of sustainability, AI can play a part in that transition. AI is of particular interest due to its capacity for transformational change and disruption and its impacts on the United Nations’ sustainable development goals (SDGs). This paper focuses on the exploration of a software project in US schools that used AI techniques to enable agility and provide healthy food options for children in schools. A key barrier to the effective management of school food programmes and nutrition is the administrative load associated with statutory compliance. Using a case study approach, the difference AI-powered tools can make in alleviating the weight of administrative processes is demonstrated. Participant observation, semi-structured interviews, and document analysis were used to inform the case study and uncover the new processes developed using the technology. An information and communication technology (ICT)-enabled boundary spanning framework is used to extend the case study towards an analysis of the systems, boundaries, relationships and perspectives which starts mapping the areas where private sector, institutions and civil society can meet to fast-track sustainable transition activities. This article presents some possible approaches to facilitating these activities, inviting policy makers to bridge the gap with businesses and use business agility to support common societal goals.